The Social-Ecological System Framework of Urban Wetlands: The Role of Collective Management at Local Level - Lida Díaz-Pinzón; Lya Sierra; Francesc Trillas; Joan Miquel Verd (International Journal of the Commons)
The social-ecological system of wetlands supports biodiversity and enhances the mental well-being of urban inhabitants. However, wetlands in Latin America face pressures from urban expansion, agriculture, governance conflicts, and poorly enforced regulations driven by economic activities, resulting in biodiversity loss and diminished ecosystem services. This study applies the social-ecological system framework to identify ecosystem services and evaluate factors influencing collective actions and governance effectiveness for urban and peri-urban wetlands. The case study is based in Cali, Colombia, using 33 semi-structured interviews, document analysis, and field visits. We find that facilitators such as leadership, networking, social capital, and community-based rules drive positive outcomes, enhancing ecosystem services. In contrast, barriers to collective action in wetland governance include low resource dependence, diverse actors, exclusion of groups, large resource size, pollution, conflicts, and property-rights issues, leading to ecosystem degradation. Additionally, our research shows how ecosystem services are influenced by environmental conflicts, property-rights systems, and community-led initiatives. Collaboration between communities and public agencies is crucial, enhancing local governance efficiency and ecosystem services.